Kontrol Diri Dengan Konformitas Pada Pelaku Judi Online - supartan, karolus; zuroida, aironi (IDEA: Jurnal Psikologi, 2023)
Online gambling is a game that is conducted using money as an internet-based bet. Lately, online gambling games often occur in the community which is triggered by the influence of friendship (conformity) and low self-control of the community. This study aims to determine how much the relationship between self-control and conformity in online gambling players. This research is quantitative research and the sampling technique uses purposive sampling technique with the criteria of being an online gambling offender aged 20-28 years old male and female. The results of the product moment correlation test obtained a value of 0.145> 0.05 (p> 0.05) which shows that there is no relationship between self-control and conformity in online gambling players. The results of the determination coefficient test obtained an R value of 0.127. This means that self-control has an effect of 12.7% on conformity in online gambling players. While 87.3% is influenced by other variables that are not in this study.